The Impact Of Brand Awareness, Product Variety, And Store Atmosphere On Consumer Purchase Intentions Towards Gen Z For Indomaret In Surabaya: The Mediating Role Of Consumer Attitude - Hongdiyanto, Charly; Perwata, Dave Michael (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to investigate the impact of product variety, store atmosphere, and brand awareness on consumer attitudes and their significant influence on purchase intentions. This study focuses on Indomaret, as the leading retail store in Surabaya with the highest outlet count and strong consumer preference. The research specifically targets Generation Z consumers aged 13 to 28, backed by data from a pre-survey conducted in February 2025. The findings offer valuable insights into the purchasing behavior of young consumers and highlight key factors that drive retail success in Surabaya's competitive market. The direct and indirect hypotheses were accepted, however, the store atmosphere variable towards purchase intention was rejected.